Isolation of Pathogenic Escherichia coli O78:K80 Serotype From Broiler Chicks with Spontaneous Pathological Conditions in Basra Province - Rajaa A.Z . Ali; Ali A.S. AL-Mayah (Kufa Journal for Veterinary Medical Sciences, 2015)
Escherichia coli(E. coli) is responsible for a variety of disease conditions which cause high economic losses in poultry due to high  mortalities, decreased food conservation rate and condemnation of whole affected carcass or organs after slaughter. In the present study, 50 out of 70 broiler birds which have been collected from diseased chickens were exhibited lesions of  fibrinousperihepatitis, fibrinous pericarditis and/or airsacculitis .Birds with these lesions were subjected for bacteriological examination.. The examination revealed isolation of 23 E. coli isolates with incidence of 46%. Concerning the virulence factors , the Congo red binding activity of these isolates reveled detection of 6 positiveisolates with incidence of 26.08%. Serotyping  showed that out of 6 Congo red positive strains, only 3 strains were serologically typed and were belonged to the serotype O78:K80. Detection of pathogenic E. coli serotypes was confirmed by PCR technique with specific primers for fimA and fimH genes. All these 3 isolates of the serotype O78:K80 were reacted with these 2 genes. Antibiogramsuscebtibility pattern displayed sensitivity of these isolates to Chloramphinicol and Gentamicin and their resistance to Amoxicillin ,Erythromycin and Nalidixic acid.